135 VITAMIN D FORTIFIED MILK—EFFECT ON VITAMIN D STATUS IN OLDER ADULTS. (18th November 2021) - O'Flaherty, N; Moloney, K; Ahmad, R; Laird, E; Hughes, C; McNulty, H; Ward, M; Strain, J J; Molloy, A M; Cunningham, C; McCarroll, K
Abstract: Background: Vitamin D fortified milk is used by some older adults to boost vitamin D status. Combined vitamin D/calcium supplements often cause gastrointestinal upset which reduces adherence. Consumption of fortified milk may be a more consistent and reliable way of increasing serum 25 hydroxyvitamin D [25(OH)D], though studies of it's efficacy in older adults are limited. Methods: We examined the vitamin D status of users of vitamin D fortified milk in participants of a longitudinal study of community dwelling Irish adults aged >60 yrs. Patients taking vitamin D supplements were excluded and independent effects were explored in multinomial regression models. Vitamin D deficiency was defined as a 25(OH)D level < 30 nmol/l. Results: 2496 participants were identified: mean age was 70.5 ± 7.0 years (range 60–96 yrs) and 145 (5.8%) reported using vitamin D fortified milk. In those who consumed fortified milk, there was a lower prevalence of vitamin D deficiency (17.9 vs 34.5%, P < 0.001). Vitamin D fortified milk also predicted less deficiency after adjusting for age, gender, season, BMI and physical frailty (OR 0.30. CI 0.19–0.48, P < 0.001). Conclusion: Vitamin D fortified milk was associated with a 70% reduction in the risk of vitamin D deficiency in older adults not taking vitamin D supplements. Findings support the use of vitamin D fortified milk as an effective means of improving vitamin D status. Fortified milk also contains additional calcium and so can be used to augment daily calcium intake.